Effects of tallow and ground flaxseed on sensory and color characteristics of ribeye steaks - LaBrune, H.J.; Hachmeister, K.A.; Kropf, Donald H.; Drouillard, James S.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forty-eight ribeye steaks from steers fed diets containing steam-flaked corn (SFC), steam-flaked corn with tallow (SFC/Tallow), or steam-flaked corn with rolled flaxseed (Flax) were used to evaluate the effects of dietary fat on sensory traits, retail display color stability, and fatty acid composition. Steaks from Flax-fed steers had increased deposition of alpha linolenic acid (C18:3n3, an omega-3 fatty acid; P<0.01) and developed a detectable off-flavor (P<0.05) when compared to those of cattle fed SFC and SFC/Tallow. There were no differences in tenderness, juiciness, or flavor intensity (P>0.10) among the three treatments. Steaks from cattle fed SFC retained a desirable color longer than those from cattle fed Flax (P<0.05) which may be attributable to premature lipid oxidation in steaks from cattle fed Flax. This study suggests that altering the fat in the diet may affect flavor and color stability of the meat. Feeding flaxseed can effectively alter composition of carcass tissues to yield beef that is high in omega-3 fatty acids, which may lead to premature lipid oxidation.
Keywords: Beef; Flaxseed; Omega-3 fatty acids; Alpha-linolenic acid; Sensory traits